Learning Management System-Based Vocabulary Instruction Management Through Total Physical Response and Adab In Action Materials for Young Learners - Siti Sholihah; Taranindya Zulhi Amalia (Managere: Indonesian Journal of Educational Management, 2026)
This study examined how LMS-based Total Physical Response vocabulary instruction using Adab in Action materials was planned, implemented, and evaluated for young learners. Vocabulary instruction for children requires engaging and developmentally appropriate strategies. However, physical participation in movement-based learning does not always indicate lexical mastery. This study employed a qualitative case study design in a nonformal English holiday program in Indonesia. Data were collected through observations and interviews and analyzed descriptively. The first finding shows that planning aligned vocabulary targets, Islamic values, LMS materials, and multimedia resources. Tutors differed in their emphasis: one prioritized character integration, while the other prioritized vocabulary mastery. The second finding reveals that implementation combined LMS input, flashcards, videos, modeling, commands, and learner responses. Familiar Adab practices supported engagement and comprehension. The third finding indicates a gap between embodied performance and verbal recall. Some learners performed actions accurately but struggled to pronounce, recall, or explain expressions. Evaluation required quizzes, oral checks, observation, and video tasks. This study highlights the implications of a digitally mediated, value-integrated Total Physical Response learning management model for improving vocabulary instruction in young learners. Future research should test this model across broader contexts using mixed-method designs.